SIMPLE APPROACH TO GROUNDWATER STUDY FOR DOMESTIC USES IN RURAL AREA - Adagunodo, T. A (university of el oued/جامعة الوادي, 2018)
Nigeria is one of the countries facing challenges associated with water supply. In rural areas, majority depend solely on hand-dug wells for their consumption which are prone to contamination. This study is aimed to determine the potability of hand-dug wells in Eyenkorin using the geophysical and physicochemical techniques. Ten Vertical Electrical Sounding (VES) data were acquired beside ten dug wells that were used for the physicochemical analysis, with half-current electrode spacing (AB/2) which varied from 46 to 75 m. The VES results revealed that water from the wells were tapped at shallow aquifers, while the hydro-physicochemical parameters revealed higher constituents of TDS, Fe2+,, K+ and NO3- in the analyzed samples. It is concluded that the contamination in the study area is as a result of anthropogenic and geogenic contributions. Water treatment is recommended in the study area prior to domestic usage
Article
Keywords: Hand-dug wells; Rural area; Nigeria; Geophysical survey; Water analysis; Groundwater study; Domestic consumption.